Newly designed superheated steam dryer bearing heat recovery unit: Analysis of energy efficiency and kinetics of Kelp drying. Issue 13 (3rd October 2018) - Jia, Zhen; Liu, Binxiong; Li, Changcheng; Fang, Ting; Chen, Jinquan
ABSTRACT: In this work, a newly designed superheated steam dryer (SSD) bearing exhaust heat recovery unit (RD) was fabricated. The dryer was designed for the superheated steam (SS) to be generated by foodstuff being dried, and the latent heat of the exhaust SS was recovered by microtube radiators and exploited to heat the RD unit. The system was then applied in Kelp drying, in which the drying kinetics was analyzed and fitted with mathematical models. The energy efficiency by the system was further evaluated and compared with hot air (HA)-drying. The results showed that the Kelp drying process in SSD could be described by two stages: heat-upstage (stage I) and superheated steam stage (stage II). While in stage I, different heat-up times of 10, 15, and 20 min were required to generate superheated steam at temperatures of 110–150°C, in stage II, the moisture content in Kelp was decreased to approximately 50 ± 5% (wet basis) within 60, 50, and 30 min at 110, 130, and 150°C, respectively. Moreover, the Midilli and Kucuk model best described Kelp drying curve in both stages, whereas the logarithmic model best fitted with that in stage II. Finally, the energy efficiency for SSD-RD was in the range of 1.127–1.425 kWh/kgwater compared with 2.406–2.508 kWh/kgwater for HA operating under the same conditions, demonstrating that the SSD-RD was able to reduce the energy input by at least 46.14%.